Options math for traders : how to pick the best option strategies for your market outlook - Nations, Scott (Wiley trading series, 2012)
A practical guide to the math behind options and how that knowledge can improve your trading performance No book on options can guarantee success, but if a trader understands and utilizes option math effectively, good things are going to happen. The idea behind Options Math for Traders + Website is to help retail option traders understand some of the basic tenants and enduring relationships of options, and option math, that professional and institutional traders rely on every day. This book skillfully highlights those strategies that are inherently superior from an option math.